PENGEMBANGAN BAHAN AJAR DIGITAL INTERAKTIF DENGAN PENDEKATAN KONTEKSTUAL PADA MATA KULIAH TEORI EKONOMI MIKRO - Yuliana FH; Siti Fatimah; Ikbal Barlian (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2021)
This study aims to develop interactive digital teaching materials using contextual approach in Microeconomic course in Economic Education Study Program, FKIP Sriwijaya University. This research and development (RnD) that used Borg and Gall development steps model, which have been modified by Sukmadinata with three stages, preliminary study, development and testing stages. The data collection techniques used observation, interview, and questionnaies. Techniques of data analysis used in development stage is desciptive analysis, and the analysis of digital teaching materials feasibility through the validation of expert judgement. Based on the teaching materials product that have been carried out by the expert judgment, the result is that in material aspect, it gets a score 82% in the verry good category, on the media aspect it gets a score 83,3% in the verry good category, and in the linguist aspect it gets a score 81%, with the verry good category. Thus it can be ignored that the digital teaching materials developed are valid and feasible to be used in the learning process